An introduction to Z-numbers with interval type-2 fuzzy TOPSIS - Nurnadiah, Zamri; Syibrah, Naim; Lazim, Abdullah; Binyamin, Yusoff (2018)
Decisions are based on ability to decide several possibilities. Decisions are uncertain, imprecise, incomplete and a challenge that is hard to meet. Z-numbers involve more uncertainties than fuzzy sets. They provide us with additional degree of freedom to represent the uncertainty and fuzziness of the real situations. In this paper, we introduce a Z-numbers with Interval Type-2 Fuzzy TOPSIS (IT2FTOPSIS) to handle uncertainty in decision problems. We provide an example to illustrate the idea of one-by-one steps Z-numbers with IT2FTOPSIS based Fuzzy Multi-Criteria Decision Making (FMCDM). The proposed method provides us with an another useful way to handle FMCDM problems in a more intelligent and flexible manner due to the fact that it uses Z-numbers and interval type-2 fuzzy sets (IT2FSs).